Performance of a pyramid solar still with stepped trays: Experimental approach - Ayman Bakry; Yaser El-Samadony; H. El-Gohari; M. Ismail (Journal of Engineering Research - Egypt)
The present experimental work aims to enhance the daily productivity of solar stills. A stepped pyramidal still with three trays was fabricated and tested under Tanta conditions, Egypt in September 2016. The still was tested with the brine feed being uninterrupted in one experiment, and with intermittent brine supply in another experiment. For continuous brine supply, the accumulated distillate was 4.95 L. For intermittent brine supply, the accumulated distillate was 4.6 L. Per unit total area, the average daily distillate water productivity is 5.5 and 5.11 L/m2 for the continuous and the intermittent feed stills, respectively. In the two ways, the still yielded a greater productivity than that of conventional pyramid solar still which is 4.4 L/m2 .